2014
DOI: 10.1158/1535-7163.mct-13-0583-t
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Inhibition of Jak Activity Inhibits Progression of Gastrointestinal Tumors in Mice

Abstract: Aberrant activation of the latent transcription factor STAT3 and its downstream targets is a common feature of epithelial-derived human cancers, including those of the gastrointestinal tract. Mouse models of gastrointestinal malignancy implicate Stat3 as a key mediator of inflammatory-driven tumorigenesis, in which its cytokine/gp130/Janus kinase (Jak)-dependent activation provides a functional link through which the microenvironment sustains tumor promotion. Although therapeutic targeting of STAT3 is highly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…The work describing AZD1480 (16) evaluated the effects of this compound and similarly showed low or no cytotoxicity in several cultured solid tumor cell lines, but tumor growth inhibition in xenografts. Similar observations of significant tumor growth inhibition of cell line xenografts that exhibited of low in vitro cytotoxicity have been made in several solid tumor models (6, 20-25, 53). The underlying reasons for these seemingly discordant results are unclear, but may be attributed to possible effects specific to conditions of 2D-cell culture or alternatively effects of the tumor microenvironment and/or disruption of a critical cytokine-mediated signaling axis, e.g., IL-6 (6, 21).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The work describing AZD1480 (16) evaluated the effects of this compound and similarly showed low or no cytotoxicity in several cultured solid tumor cell lines, but tumor growth inhibition in xenografts. Similar observations of significant tumor growth inhibition of cell line xenografts that exhibited of low in vitro cytotoxicity have been made in several solid tumor models (6, 20-25, 53). The underlying reasons for these seemingly discordant results are unclear, but may be attributed to possible effects specific to conditions of 2D-cell culture or alternatively effects of the tumor microenvironment and/or disruption of a critical cytokine-mediated signaling axis, e.g., IL-6 (6, 21).…”
Section: Discussionsupporting
confidence: 80%
“…As JAKs are key upstream mediators of STAT3 activation in solid tumors (16), we sought to determine the effects of targeted inhibition of JAKs on STAT3 activation in cell culture and mouse models of OC. To evaluate the effects of JAK/STAT3 pathway inhibition on viability, apoptosis and proliferation of OC cells, the small molecule inhibitor AZD1480 was chosen based on its potent JAK1/2-selective activity and inhibition of STAT3 signaling in several solid tumor models and have been used successfully in models of other solid tumors (6, 20-25). Exposure of human (A1847, OVCAR-5 and OVCAR-8) and murine (MOVCAR-5009 and MOVCAR-5447) OC cells to increasing concentrations of AZD1480 (0, 0.05, 0.1, 1, 5 and 10 μmol/L) for 24 hours resulted in dose dependent inhibition of STAT3 activation, measured by evaluating pSTAT3 Y705 levels by immunoblot analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, where adverse (on target) effects were reported for JAK inhibitors, they included anemia, neutropenia, and thrombocytopenia (68). Predictably, JAK1/2 inhibitors, such as AZD1480, impair GP130 signaling, and reduce colitis-associated colon and inflammation-associated GC development in mice (69). We have shown that this occurs through inhibition of STAT3 signaling in the epithelium (69), while others found that AZD1480 also reduced the abundance of tumor-associated myeloid cells and tumor angiogenesis (70).…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…When combined with routine endoscopic monitoring and the intervention strategies outlined here, these protocols will provide powerful pre-clinical insight into the efficacy of therapeutics. Our laboratories routinely use all of these protocols to monitor the success of novel therapeutics 10,23,24 .…”
Section: Discussionmentioning
confidence: 99%